Combining Optimum Propeller Design on Roro Ship Re-engine - I Made Arina; Adhi Iswantoro; Salsabilla Aulia Fitri (Department of Naval Architecture - Diponegoro University, 2023)
Passenger ships serve several areas in Indonesia, one of which is KMP (Kapal Motor Penumpang) Dharma Rucitra 3. In 2020 this ship had an accident and almost sank, then causing the main engine to submerge. With this problem, it is necessary to repower with the engine provided by the company, by replacing the old engine with a new engine. The new engine namely Yanmar 6N21A SV with a power of 1200 HP at 850 RPM. Initially the ship's speed was 12 knots with the data of Makita GNLH 630M engine with a power of 1300 HP at 375 RPM with a B4-50 propeller. To achieve the desired speed, it is necessary to have an optimal propeller to improve engine performance. In this research, an algorithm has been specially developed to find the optimum propeller design of B-series propellers for KMP Dharma Rucitra 3 by defining the overall parameters of a propeller like diameter, pitch-ratio, blade area ratio and the number of blades. The optimum propeller design is performed as multi-objective function to constraints imposed by propeller parameters. The computer program has been developed to select the optimum propeller by considering the boundary condition of system, hull-propeller interactions, and engine-propeller matching (EPM). This research also carried out open water and self-propulsion simulations using computational fluid dynamics (CFD). Then it can be concluded that the development of an algorithm to optimize the selection of propellers on KMP Dharma Rucitra 3 obtained propellers with B4-49.6 type with a diameter of 1,995 m so that it can reach a speed of 14,2 knots at 85% maximum continuous rating of engine power.